Direct anterior approach total hip arthroplasty for Crowe III and IV dysplasia - Zaiyang Liu, MD; Courtney D. Bell, MD; Alvin C. Ong, MD; Songtao Wu, MD; Ziqiang Li, MD; Yuan Zhang, MD (Arthroplasty Today, 2020)
High-dislocated hip dysplasia is challenging to treat with total hip arthroplasty via the direct anterior approach (DAA). The DAA has potential advantages including optimizing component positioning, enhanced hip stability, and a more rapid postoperative recovery. We present a surgical technique for DAA total hip arthroplasty for hip dysplasia that includes preoperative planning, soft tissue releases, subtrochanteric osteotomy, component placement, and intraoperative nerve monitoring and imaging. This technique provides detailed technical instructions, specifically including pearls and pitfalls, and complication prevention strategies.